Peran Penyuluh Pertanian dalam Pengembangan Kelompok Tani Tanaman Kopi di Kecamatan Silih Nara Kabupaten Aceh Tengah - Nurdin Bahtra; Mujiburrahmad Mujiburrahmad; Otto Nur Abdullah (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
The purpose of agricultural extension is to produce competent human resources for agricultural development actors so that they are able to build strong agricultural businesses, do better farming (better farming), make farming more profitable (better businesses), live more prosperously (better living) and a healthier environment. This study aims to find out about the role of extension workers and their constraints. This research was conducted by taking data through interviews with extension workers and the results of filling out questionnaires by 33 members of the farmer group. The results of the study concluded that extension workers played a very important role in agricultural extension in Bius Baru village as mentors, organizers/ dynamizers, technicians, consultants, educators, leaders and advisors. Farmer groups have developed with routine activities and assignments, adequate facilities, farming experience, group norms and rules and group classes. The constraints of extension workers in developing farmer groups are: participation of members of farmer groups is still low, members of farmer groups are not consistent in attending meetings where some are present and others are not present, low motivation of farmers to become more advanced and infrastructure that is not yet adequate. Farmers' constraints are: field coordination, most farmers have side jobs, use of farmer group facilities and discontinuous meeting times.